Pertimbangan Hakim Dalam Menjatuhkan Putusan Vrijspraak Terhadap Pengedar Narkotika Jenis Sabu (Studi Putusan Nomor : 13/Pid. Sus/2022/Pn.Tjk) - Prasetyawati, Endang; Satria, Indah; Destika , Nadya (Yuriska: Jurnal Ilmiah Hukum, 2023)
The abuse of drugs and illegal drugs (drugs) in Indonesia in recent years has become a serious and alarming problem, so it has become a national problem. At issue in this study is the judge's consideration in applying the Vrijspraak ruling on the distribution of mind-altering methamphetamine and the application of criminal law to mind-altering methamphetamine traffickers. research decision number:13/Pid.Sus/2022/PN.Tjk, the research method used is legal and empirical, the research results are based on the legal details revealed during the trial that the prosecutors The prosecutor's failure to prove his accusation made the judge doubtful about the prosecutor's indictment, and the witnesses all denied having a relationship with the accused and the application of criminal law to drug dealers. god direction. death penalty and a fine of Rp 10,000,000,000 (ten billion rupees).